Induction of humoral and cell-mediated immunity to the NS1 protein of TBEV with recombinant Influenza virus and MVA affords partial protection against lethal TBEV infection in mice - Beicht, Jana; Kubinski, Mareike; Zdora, Isabel; Puff, Christina; Biermann, Jeannine; Gerlach, Thomas; Baumgärtner, Wolfgang; Sutter, Gerd; Osterhaus, Albert D. M. E.; Prajeeth, Chittappen Kandiyil; Rimmelzwaan, Guus F. (Frontiers in Immunology, 2023)
Tick-borne encephalitis virus (TBEV) is one of the most relevant tick-transmitted neurotropic arboviruses in Europe and Asia and the causative agent of tick-borne encephalitis (TBE). Annually more than 10,000 TBE cases are reported despite having vaccines available. In Europe, the vaccines FSME-IMMUN® and Encepur® based on formaldehyde-inactivated whole viruses are licensed. However, demanding vaccination schedules contribute to sub-optimal vaccination uptake and breakthrough infections have been reported repeatedly. Due to its immunogenic properties as well as its role in viral replication and disease pathogenesis, the non-structural protein 1 (NS1) of flaviviruses has become of interest for non-virion based flavivirus vaccine candidates in recent years. Therefore, immunogenicity and protective efficacy of TBEV NS1 expressed by neuraminidase (NA)-deficient Influenza A virus (IAV) or Modified Vaccinia virus Ankara (MVA) vectors were investigated in this study. With these recombinant viral vectors TBEV NS1-specific antibody and T cell responses were 2 This is a provisional file, not the final typeset article induced. Upon heterologous prime/boost regimens partial protection against lethal TBEV challenge infection was afforded in mice, supporting the inclusion of NS1 as a vaccine component in next generation TBEV vaccines.